Appendix 2. Average Yearly Potato Production Statistics for Potatoes Produced at the UF/IFAS PSREU Hastings Farm - Chad M. Hutchinson; Doug Gergela (EDIS)
This is a multi-chapter report by C.M. Hutchinson and Doug Gergela. In the process of being published by the UF Department of Horticultural Sciences, January-July 2007.